(untitled) (Jurnal Pembangunan Sosial, 2010)
Bidaah based on superstitious beliefs such as belief in ghosts and spirits are very common among some of the Malay community. These beliefs unfortunately will lead to the practice of bidaah that can lead to the perversion of the Islamic faith which is infamously known as bid’ah dalalah. Examples of bidaah dalalah which are being frequently practiced by Muslims in Malaysia due the use of amulets and menilik which may lead to disbelief to God. What is of concern, such practices exist in the process of perbomohan such as the use of the jinn, the worship of evil spirits and so on. Ultimately, this paper will explore the concept and various forms of bidaah dalalah as well as its practice in the Malay society.